Profil Sensori Sediaan Pemanis dengan Metode Rate-All-That-Apply (RATA) - Dede Robiatul Adawiyah; Olivia Mellyana Tjiptoputri; Lince Lince (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
Sweetener is food additive consisting of natural sweetener and artificial sweetener which give sweet sensation to food products. Table-top sweeteners are sought due to its advantages in comparison to sugar, which is giving off sweet sensation in food with no or low calorie. This is proven useful for people who suffer from illnesses, such as diabetes mellitus, obesity, and sensitive tooth. This need should be supported by development of table-top sweeteners to satisfy consumer preferences. Rate-All-That-Apply (RATA) is a consumer based test developed from Check-All-That-Apply (CATA). The objective of this research is to study sensory profiles of various table-top sweeteners based on diabetic and non-diabetic consumer and its intensity, as well as identifying attributes which determines consumer preference. There were six table-top sweeteners used in this study with three group of panelists based on their medical history. The research result revealed that sweetener A was identic to the attribute cooling, sweet aftertaste, sweet, body thickness, licorice, and mouth drying. Sweetener C and F were identic to the attribute metallic aftertaste, bitter aftertaste, bitter, and metallic. Diabetics give the most hedonic score above the average value to Sweetener A, B, and D. Non-diabetics with a heredity of diabetes give the most hedonic score above the average value to Sweetener B. Non-diabetics without a heredity of diabetes give the most hedonic score above the average value to Sweetener D and E. Generally, consumer could not identify attributes which determines their preference, however they could define unwanted attributes in table-top sweeteners, which are bitter, bitter aftertaste, metallic, metallic aftertaste, and mouth drying.